From HUPPAAL to UPPAAL - A Translation from Hierarchical Timed Automata to Flat Timed Automata - David, Alexandre; Möller, M. Oliver (BRICS Report Series, 2001)
We present a hierarchical version of timed automata, equipped with data types, hand-shake synchronization, and local variables. We describe the formal semantics of this hierarchical timed automata (HTA) formalism in terms of a transition system. We report on the implementation of a flattening algorithm, that translates our formalism to a network of Uppaal timed automata. We establish a correspondence between symbolic states of an HTA and its translations, and thus are able to make use of Uppaal’s simulator and model checking engine. This technique is exemplified with a cardiac pacemaker model. Here, the overhead introduced by the translation is tolerable. We give run-time data for deadlock checking, timed reachability, and timed response analysis.